Phenotype and Genotype Expression with the GDF9 Gene in the Sapudi and Garut Sheeps - Hairoh, Nikhmatul; Mudawamah, Mudawamah; Sumartono, Sumartono (TERNAK TROPIKA Journal of Tropical Animal Production, 2023)
This study aims to determine the expression of phenotypes and genotypes in Sapudi and Garut sheep, as well as differences between GDF9 exon 1 gene expression and phenotypic traits in Sapudi and Garut sheep. The research method used is a quantitative descriptive method. The material used was 48 rams kept at UPT Breeding Cattle and Forages in Jember and Seribu Pulau Children's Farm, Kangploso Farm, Malang. As for the observation of GDF9 gene expression by qPCR analysis using GDF9 gene primers with a sample of 8 tails. Data analysis used unpaired t-test analysis and continued with the BNT test. Observation of phenotypic traits included body length (PB), chest circumference (LD), and body height (TB). The genotype observed was GDF9 gene expression. The results showed very significant differences in the phenotypic characteristics of the Sapudi and Garut sheep (P<0.01). Based on the study, there were differences in the expression of the phenotypic traits of Sapudi and Garut sheep on body length (Sapudi 63.21a ± 3.39; Garut 77.71b ± 5.66) cm, chest circumference (Sapudi 76.15a ± 3.81; Garut 83, 00b ± 8.75) cm and height (Sapudi 64.96a ± 3.97; Garut 73.50b ± 5.60) cm. There was a very significant difference (P<0.01) in genotypic traits from the qPCR results of the GDF9 gene between sheep breeds, namely Sapudi sheep 31.66 ± 5.61 and Garut sheep 23.70 ± 2.40.